2004
DOI: 10.1002/cncr.20186
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of fine‐needle aspiration cytology and frozen section in primary parotid carcinoma

Abstract: BACKGROUND The low incidence and histologic heterogeneity of primary parotid carcinomas makes it difficult to evaluate the value of preoperative fine‐needle aspiration cytology (FNAC) and intraoperative frozen section (FS) analysis. In the current study, the authors reviewed a single institution's experience regarding the preoperative and intraoperative diagnostic value of FNAC and FS in primary salivary gland carcinomas. METHODS Between January 1990 and December 2002, 108 primary parotid carcinomas were resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
125
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(141 citation statements)
references
References 49 publications
2
125
1
2
Order By: Relevance
“…As we demonstrated previously, the combination of negative malignancy cytology result in absence of clinic-imaging signs indicative of a primary parotid malignancy (irregular borders, tumor size, and Journal of Surgical Oncology heterogeneity of US and/or CT scan) could decrease the possibility of a false-negative result with better À LR regarding carcinoma. On the other hand, high specificity and þ LR are obtained in terms of primary parotid malignancy, with good exact diagnosis frequency (58%), and this information, combined with frozen section analyses as noted by Zbaren et al [7] and Lin and Bhattacharyya [5], could give a better definition of surgical strategy for determination of surgical margins, tumor grade, extent of neoplasm and the consequent need for neck dissection, and extensive or conservative procedures (total vs. lateral parotidectomy, total vs. radical parotidectomy).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As we demonstrated previously, the combination of negative malignancy cytology result in absence of clinic-imaging signs indicative of a primary parotid malignancy (irregular borders, tumor size, and Journal of Surgical Oncology heterogeneity of US and/or CT scan) could decrease the possibility of a false-negative result with better À LR regarding carcinoma. On the other hand, high specificity and þ LR are obtained in terms of primary parotid malignancy, with good exact diagnosis frequency (58%), and this information, combined with frozen section analyses as noted by Zbaren et al [7] and Lin and Bhattacharyya [5], could give a better definition of surgical strategy for determination of surgical margins, tumor grade, extent of neoplasm and the consequent need for neck dissection, and extensive or conservative procedures (total vs. lateral parotidectomy, total vs. radical parotidectomy).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, final objective of FNAB has ranged from preoperative prediction of histopathological diagnosis to a ruling-out-malignancy role [6]. In this context, some authors mention the feasibility to change the actual management strategy of parotid neoplasms in the transoperative setting, with the combination of the FNAB test, the frozen section study, and surgical findings [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…FS analysis of salivary gland tumors has traditionally been used to identify or exclude malignancy and to type the salivary gland lesion. Some authors advocated that FS is superior to FNA for the reason that FNA cannot be relied upon to type or grade malignant salivary gland tumors and FNA should not be used as the sole determinant of surgical management for primary parotid carcinomas (Zbaren et al, 2004). Whereas, some studies found that FNA is more sensitivity, FS is more specific but both FS and FNA provide a similar accuracy (Layfield et al, 1987;Seethala et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the biopsy is invasive, and the results are not always conclusive. 4 Therefore, pre-operative imaging plays an important role in treatment selection and surgical planning. CT and conventional MRI are used to localize lingual masses and delineate their extent.…”
Section: Introductionmentioning
confidence: 99%